Magnificent voyagers the U.S. exploring expedition, 1838-1842 - Viola, Herman J.; Margolis, Carolyn; Viola, Herman J.; Margolis, Carolyn (Washington, D.C. Smithsonian Institution Press, 1985)
Account of the activities, chronology, mapping and botanical and zoological collections of the United States Exploring Expedition of 1838-1842, which mapped 1500 miles of the Antarctic coast and proved that the continent exists. Published in connection with the exhibition 'Magnificent Voyagers' organized by the National Museum of Natural History and circulated by the Smithsonian Institution, Washington, D.C.
The story of the U.S. exploring expedition Herman J. Viola -- Expedition botany : the making of a new profession Richard H. Eyde -- Vertebrate collections : lost opportunities George E. Watson -- The invertebrates of the U.S. Exploring Expedition Frederick M. Bayer -- James Dwight Dana and Pacific geology Daniel E. Appleman -- Anthropology and the U.S. Exploring Expedition Adrienne L. Kaeppler -- Ships and squadron logistics Philip K. Lundeberg -- Surveying and charting the Pacific basin Ralph E. Ehrenberg, John A. Wolter, and Charles A. Burroughs -- Charles Wilkes : a biography Joye Leonhart -- Charles Wilkes as diplomat E. Jeffrey Stann -- The National Gallery at the Patent Office Douglas E. Evelyn -- The Exploring Expedition and the Smithsonian Institution Nathan Reingold and Marc Rothenberg.
Maps on lining papers.
Includes bibliographical references (pages 271-285) and index.